Skogsvårdsentreprenörers uppfattning om SÖDRA som uppdragsgivare - Petersson, Sofie (SLU/School for Forest Management, 2015)
Södra in Oskarström has the ambition to become the best client for silviculture contractors and another aim is that the contractors should feel a strong sense of community with Södra. Several factors play an important role in order for these ambitions to be realized. The purpose of this study was to investigate how the contractors feel about their business relationship with Södra. The study was conducted during the spring of 2015 through a questionnaire which was sent to all ten silviculture contractors working with Södra in Oskarström. Overall, it seemed like the contractors were satisfied with the collaboration. They were also well informed about Södra´s forest management standards. There were two elements that the contractors were less satisfied with and they were the feedback regarding performed actions, as well as the markings of the treatment units.